An Overview on Wavelets in Source Coding, Communications, and Networks. (26th June 2007) - Fowler, James E.; Pesquet-Popescu, Béatrice
Abstract : The use of wavelets in the broad areas of source coding, communications, and networks is surveyed. Specifically, the impact of wavelets and wavelet theory in image coding, video coding, image interpolation, image-adaptive lifting transforms, multiple-description coding, and joint source-channel coding is overviewed. Recent contributions in these areas arising in subsequent papers of the present special issue are described.